2003
DOI: 10.1038/nature02007
|View full text |Cite
|
Sign up to set email alerts
|

Planning for smallpox outbreaks

Abstract: Mathematical models of viral transmission and control are important tools for assessing the threat posed by deliberate release of the smallpox virus and the best means of containing an outbreak. Models must balance biological realism against limitations of knowledge, and uncertainties need to be accurately communicated to policy-makers. Smallpox poses the particular challenge that key biological, social and spatial factors affecting disease spread in contemporary populations must be elucidated largely from his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
271
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(280 citation statements)
references
References 27 publications
2
271
1
2
Order By: Relevance
“…A recent review article (Ferguson et al, 2003) identified several ways in which social structure has been introduced to smallpox models. A common approach is to define subpopulations based on age or socio-economic factors or, in patch models, geographic factors.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review article (Ferguson et al, 2003) identified several ways in which social structure has been introduced to smallpox models. A common approach is to define subpopulations based on age or socio-economic factors or, in patch models, geographic factors.…”
Section: Introductionmentioning
confidence: 99%
“…We get s k = δ/γ which is a turning point of the random function in (9). From (10), we can see that, for every k = 1, .…”
Section: The Effect Of Randomness On the Size Of An Epidemicmentioning
confidence: 99%
“…The SIR epidemic model has been used in different forms for studying epidemiological processes such as the spread of HIV 7 , influenza 8 and even smallpox 9 . Indeed, there are various forms of the SIR model including SEIR, SIS, SIRS, and SVIR 4 .…”
Section: The Sir Epidemic Modelmentioning
confidence: 99%
“…This concern has been reflected in studies that model and evaluate possible response policies against smallpox [1][2][3][4][5][6][7][8]. A review of recent smallpox models, including a classification, is presented by Furgeson et al [7].…”
Section: Introductionmentioning
confidence: 99%